2011
DOI: 10.4318/tjg.2011.0237
|View full text |Cite
|
Sign up to set email alerts
|

A new risk factor for the development of non-alcoholic fatty liver disease: HLA complex genes

Abstract: (33 erkek, ortalama yafl: 53,8 [yafl aral›¤›, 32-77]) ve ultrasonografisi normal 50 verici aday› kontrol grubu olarak al›nd› (20 erkek, ortalama yafl: 44,6 [yafl aral›¤›, 26-71] (33 male, median age: 53.8 [range, 32-77 years]) by means of ultrasonography data, and 50 individuals, whose ultrasonography data did not show hepatosteatosis, comprised the control group (20 male, median age: 44.6 [range, 26-71 years]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This result strongly suggests that the modification in MHC II gene expression affected neither ALT nor AST levels, consistent to their comparable liver histology between groups. It has been, however, suggested that some alleles in MHC II pathway were associated with a severity of NAFLD and ALT, but not AST levels, in a Turkish population [33]. In this study, the investigators could not assess a presence of NASH in the population.…”
Section: Discussionmentioning
confidence: 83%
“…This result strongly suggests that the modification in MHC II gene expression affected neither ALT nor AST levels, consistent to their comparable liver histology between groups. It has been, however, suggested that some alleles in MHC II pathway were associated with a severity of NAFLD and ALT, but not AST levels, in a Turkish population [33]. In this study, the investigators could not assess a presence of NASH in the population.…”
Section: Discussionmentioning
confidence: 83%
“…[1517] HLA loci are highly polymorphic and may confer greater risk for NASH and NASH-related cirrhosis. [2,4,5] In the present study, we have examined for genetic predisposition for NASH and advanced fibrosis within the HLA loci among biopsy-proven NAFLD and its subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, HLA-B∗65 has been shown to be independently associated with the development of NAFLD. [2] Furthermore, HLA-B∗35 and -B∗40 have been linked to the development of cirrhosis in patients with alcoholic fatty liver disease. [3–5] Within the HLA class II, HLA- DQ5 has been significantly associated with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, HLA-DRB1*04, HLA-DQB1*0401/2, and TNFA*1 (-308) were associated with disease resistance [2]. Furthermore, initial studies on the role of genetic factors in susceptibility to non-alcoholic fatty liver disease point toward an important role of human leukocyte antigen in the pathogenesis of non-alcoholic fatty liver disease [3].…”
Section: To the Editormentioning
confidence: 99%